2023
DOI: 10.1002/ps.7481
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and antifungal evaluation of phenylthiazole‐1,3,4‐oxadiazole thione (ketone) derivatives inspired by natural thiasporine A

Abstract: BACKGROUNDPlant pathogenic fungal infections have become a severe threat to the yield and quality of agricultural products, and new green antifungal agents with high efficiency and low toxicity are needed. In this study, a series of thiasporine A derivatives containing phenylthiazole‐1,3,4‐oxadiazole thione (ketone) structures were designed and synthesized, and their antifungal activities against six invasive and highly destructive phytopathogenic fungi were evaluated.RESULTSThe results found that all compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Some derivatives showed potent antifungal activities against some phytopathogenic fungi. For example, derivatives e and f showed significant antifungal activities against Sclerotinia sclerotiorum, with EC 50 values of 0.22 µg/mL and 0.39 µg/mL, respectively, which were superior to that of the commercial fungicide carbendazim (0.70 µg/mL) [18]. The above results demonstrated that phenylthiazole is a promising antifungal skeleton for discovering new fungicides.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Some derivatives showed potent antifungal activities against some phytopathogenic fungi. For example, derivatives e and f showed significant antifungal activities against Sclerotinia sclerotiorum, with EC 50 values of 0.22 µg/mL and 0.39 µg/mL, respectively, which were superior to that of the commercial fungicide carbendazim (0.70 µg/mL) [18]. The above results demonstrated that phenylthiazole is a promising antifungal skeleton for discovering new fungicides.…”
Section: Introductionmentioning
confidence: 81%
“…Satisfactorily, some novel compounds with potent antifungal activity against M. oryzae and the SAR results were obtained in this study. In our previous study, most phenylthiazole derivatives mainly showed excellent antifungal activities against S. sclerotiorum and S. rolfsii [15,16,18]. Only phenylthiazole derivatives bearing amide moiety showed good antifungal activity against M. oryzae.…”
Section: Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we synthesized several series of thiasporine A derivatives with potent antifungal activity and demonstrated that phenylthiazole was a promising antifungal activity skeleton [ 16 ]. Notably, Shi [ 17 ] introduced an 1,3,4-oxadiazole thione into phenylthiazole to synthesize compound E1 ( Figure 1 ), exhibiting the most excellent antifungal activity against S. sclerotiorum with an EC50 value of 0.22 μg/mL, which was superior to that of the commercial fungicide Carbendazim (EC 50 = 0.70 μg/mL). Regrettably, compound E1 did not perform excellent antibacterial activity, but this result provides valuable guidance for carrying out subsequent molecular design.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been applied to control rice sheath blight, with chemical control such as fungicides being widely utilized as an effective control measure. , Unfortunately, the intensive and continuous utilization of common fungicides increases the risk of resistance development of the pathogen, which severely restricts the application of these fungicides. , Thus, there is an urgent need for high-efficiency, environmentally friendly, and low-toxic fungicides against R. solani. …”
Section: Introductionmentioning
confidence: 99%